LEGAL OPPORTUNITIES OF BANK INTERESTS: REINVENTING ANALYSIS OF THE MASHLAHAT THEORY OF AL-SYATHIBI - Sadat, Anwar (Al-Ulum, 2015)
This study described the analysis of legal opportunities in a bank saving interest. In general, banks in Indonesia are very influential on the dynamics of the economic life of society. Existence evenly spread to remote. This has implications on the ease of access and services to the wider community. If the determination of the bank savings raised interest prohibition, can lead to economic turmoil in the form of a massive diversion of funds by customers that can systemically affect the stability of national economy. Considering the majority of government agencies (including ministries of religion) and private sectors to accommodate the livelihood of the general public, especially civil servants and private employees, which is increasingly dependent on the existence of a conventional bank. Mashlahat theory put forward by al-Syatibi can provide legal opportunities, both macro (general) and micro (personal). In this study, the author find that there are legal opportunities of bank savings interest in the analysis al-Syatibis theory of MashlahatÂ -----Kajian ini menjelaskan tentang sejumlah analisis peluang hukum bunga tabungan pada bank. Pada umumnya, bank di Indonesia sangat berpengaruh terhadap dinamika kehidupan ekonomi masyarakat. Eksistensinya menyebar secara merata hingga ke pelosok. Hal ini berimplikasi pada kemudahan akses dan pelayanan pada masyarakat luas. Jika penetapan keharaman bunga tabungan bank dimunculkan, dapat mengakibatkan gejolak ekonomi berupa pengalihan dana besar-besaran oleh nasabah yang dapat berdampak secara sistemik terhadap stabilitas ekonomi nasional. Menimbang sebagian besar instansi pemerintah (termasuk kementerian agama) maupun swasta yang mengakomodasi hajat hidup masyarakat luas, khususnya pegawai negeri dan pegawai swasta, yang semakin tergantung dengan eksistensi bank konvensional. Teori Mashlahat yang dikemukakan al-SyÄtibÄ« dapat memberikan peluang hukum, baik secara makro (umum) maupun mikro (pribadi). Dalam kajian ini, penulis menemukan adanya peluang hukum bunga tabungan bank perspektif analisis teori Mashlahat